Are Steroids Still Useful in Immunosuppressed Patients With Inflammatory Bowel Disease? A Retrospective, Population-Based Study - Sicilia, Beatriz; Arias, Lara; Hontoria, Gadea; García, Nieves; Badia, Ester; Gomollón, Fernando (Frontiers in Medicine, 2021)
BACKGROUND: Efficacy of corticosteroids in immunosuppressed patients with inflammatory bowel disease (IBD) have not been elucidated AIMS: To determine the efficacy and examine the long-term follow-up of systemic or low-bioavailability oral steroid treatment for moderate flare-ups in patients who received at least 6 months of immunosuppressive treatment. METHODS: Immunosuppressed patients with inflammatory bowel disease (IBD) from our population-data registry were analyzed. For statistical analysis, the chi-square test, Mann-Whitney U test, and Kaplan-Meier survival analysis were used. RESULTS: A total of 392 patients with IBD and a median of 82 (range, 6-271) months of immunosuppressive (IMM) treatment were identified. The mean follow-up was 87 months (range, 6-239 months). A total of 89 patients (23%) needed at least one steroid treatment during their follow-up. Average time from IMM to steroid treatment was 26 (range, 6-207) months. In patients with CD, fibrostenotic (B2) and fistulizing (B3) behaviors [p=0.005; odds ratio (OR): 2.284] were risk factors for using steroids after IMM treatment. In patients with UC, no statistically significant variables were identified. Of the 89 patients who received steroid treatment, 49 (55%) needed biological treatment or surgery after a median of 13 months (range, 0-178), 19 (21%) needed more than one steroid treatment, and 31 (35%) required no further treatment. Patients with CD had a higher risk (p=0.007; OR: 3.529) of receiving biological treatment or surgery than patients with UC. The longer the patients with UC (more months) spent using steroids, the greater the risk of requiring treatment with biological drugs or surgery (p=0.009). We noted that the 75% probability of rescue therapy was 62 months for patients with UC versus 36 months for patients with CD, although the difference was not statistically significant (p=0.078). CONCLUSION: A total of 23% of the immunosuppressed patients with IBD needed at least 1 steroid treatment. B2-B3 behavior predicted steroid treatment in patients with CD, and they had a 3.5 times higher risk of receiving biological treatment or surgery after steroid treatment and required earlier treatment than patients with UC. Only 35% of patients who needed steroid treatment after IMM treatment required no further rescue therapy.